Analysis of Vibration in Payload Room Due to Engine Vibration on LSU-05 NG - Wijaya, Yusuf Giri; Ula, Nur Mufidatul; Muksin, M.; Pratama, Mukhael Gilang Pribadi Putra (Computational And Experimental Research In Materials And Renewable Energy, 2021)
LSU-05 NG is one of the unmanned air vehicles (UAV) developed by the aviation technology center LAPAN. The LAPAN aviation technology center designed the LSU-05 NG to be able to carry a larger payload and broader range than other types of LSUs. Therefore, the LSU-05 NG uses an engine that has enough power. LSU-05 NG uses a piston-type engine with a capacity of 170 CC. UAV engine is the primary source of vibration in the UAV structure. Excessive vibration can cause damage to the UAV structure and malfunction of the UAV payload, such as sensors, control systems, and cameras. In this research, vibration measurements were carried out at 2 locations. The measurement location is on the engine and where the payload is installed. The vibration measurement on the LSU-05 NG was carried out during the ground test. The accelerometer sensor is used to measure vibrations and is connected to the NI data acquisition system and displayed with LabVIEW. The data to be taken are acceleration and frequency data with variations in the RPM value on the LSU-05 NG engine. With these measurements, the vibration characteristics caused by the engine in the LSU-05 NG structure, primarily where the payload is stored, can be known.